From Uninterruptible Power Supply to resilient smart micro grid: The case of a battery storage at telecommunication station. (April 2020) - Ferraro, M.; Brunaccini, G.; Sergi, F.; Aloisio, D.; Randazzo, N.; Antonucci, V.
Highlights: UPS energy storage exploited to provide ancillary services to power grid. Different storage hardware and control software configurations were simulated and analyzed. Artificial intelligence to convert UPS system into resilient power supply in smart microgrid. Economic assessment was performed in terms of energy costs. Abstract: Nowadays, resilient grids meet growing interest for their capability of supplying critical load even in case of power fault coming from grid disturbance and natural disasters. To do this, such grids involve redundant apparatus and predictive control schemes. For high value services, unexpected system unavailability is source of economic losses to the providers. Hence, beside the internal energy storage devices, such plants had better to have redundancy of energy sources (e.g. electrical grid and natural gas network) and tailored power flows control strategies still valid even in the case of energy shortage. On the other hand, distributed storage resources is attracting growing interest to support the power networks in terms of both resiliency and flexibility facing the impact of generation from the Renewable Energy Sources. In this work, a power supply system controller based on Artificial Intelligence was developed and simulated to wisely operate the storage resources to serve the ICT equipment as Uninterruptible Power Supply (above all in case of emergency) as fundamental mission. Secondly, the investigation assessed the capability, to offer ancillary services to the power network increasing its resiliency measured system response in terms of survival time during grid faults and restoration transient time to recover initial service level.